2003
DOI: 10.1113/jphysiol.2003.041269
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the modulation of K+ currents in diabetic rat cardiac myocytes

Abstract: A transient (Ipeak) and a sustained (Isus) outward K+ current were measured, using whole‐cell voltage‐clamp methods, in isolated rat ventricular myocytes obtained by enzymatic dispersion. A comparison was made between male and female rats following induction of (insulin‐deficient) diabetes with streptozotocin (STZ). In control (non‐diabetic) rats, both currents were smaller in cells obtained from females, as compared to males (P < 0.005). However, whereas inducing diabetes in male rats significantly attenuated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 42 publications
3
38
0
Order By: Relevance
“…Earlier work from our laboratory showed that cardiac angiotensin II levels and oxidative stress are increased in diabetic male hearts (41, 43). These changes are reduced or absent in diabetic females (41)(42)(43). Earlier work from our laboratory also showed that in vivo treatment of male rats with an angiotensin-converting enzyme (ACE) inhibitor reduces or prevents diabetes-induced increase in angiotensin II and the resulting oxidative stress (41).…”
Section: Gender Differences In Conductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Earlier work from our laboratory showed that cardiac angiotensin II levels and oxidative stress are increased in diabetic male hearts (41, 43). These changes are reduced or absent in diabetic females (41)(42)(43). Earlier work from our laboratory also showed that in vivo treatment of male rats with an angiotensin-converting enzyme (ACE) inhibitor reduces or prevents diabetes-induced increase in angiotensin II and the resulting oxidative stress (41).…”
Section: Gender Differences In Conductionmentioning
confidence: 72%
“…Using animal models of diabetes, we have found that an upregulated cardiac renin-angiotensin system (RAS) (10,13) contributes to the potentially arrhythmogenic attenuation of K ϩ currents and to action potential prolongation (40). We also identified sex differences in K ϩ -current modulation (42), partly attributed to selective activation of the cardiac RAS. Selective activation results in lower cellular angiotensin II levels in diabetic female hearts compared with diabetic male hearts (43).…”
mentioning
confidence: 89%
“…For example, streptozotocin-induced diabetes depresses the rate of ventricular pressure development and prolongs the contraction and relaxation phases to a greater degree in papillary muscles from males than in those from females [12,28]. Also, in type 1 diabetic rats, the ventricular myocyte action potential is prolonged, corresponding to a decline in peak potassium currents in males but not in females [29,30]. Similar attenuation of peak potassium currents in males but not females is seen in ventricular myocytes from the db/db mouse model of type 2 diabetes with obesity [31], although whole-heart function is impaired to a similar degree in both sexes [32].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, in vitro incubation with 17␤-estradiol was found to augment these currents, presumably due to suppression of the reninangiotensin system. However, this effect was inhibited by addition of ANG II (35).…”
mentioning
confidence: 87%
“…More recently, we determined that there is a striking gender dependence associated with this effect (35). In myocytes from streptozotocin (STZ)-treated diabetic females, K ϩ currents were not affected by ACE inhibition.…”
mentioning
confidence: 99%